Reading rhetorical texts : an introduction to criticism - Andrews, James Robertson, 1936-; Leff, Michael C.; Terrill, Robert (Boston : Houghton Mifflin, 1997)
This book is divided into four parts: Critical Foundations; Critical Readings and Commentary; Alternative Readings; and Critical Reading: Sample Studies.
Keywords: Rhetoric; American Speeches; Speeches, addresses, etc., American -- History and criticism; English language -- United States -- Rhetoric